THE EARLY ENGLISH FACTORIES OF SOUTH WEST INDIA: A HISTORICAL ARCHAEOLOGY PERSPECTIVE - MASON PAUL MACKENZIE (DURHAM UNIVERSITY, 2014)
This thesis presents a historical archaeology perspective on 17 th -century Anglo-Indian trade, focussing on twelve factories established in south-west India by the East India Company and a rival body of merchants known as the Courteen Association. The thesis breaks down into three parts. The first chapter defines the parameters, research aims and limitations of the study, before presenting a review of the existing corpus of relevant published literature. The historic background for the period follows in Chapter 2 together with an appraisal of archaeological comparison sites. The second part of the thesis (Chapters 3-7) sets out the documentary, cartographic, pictorial and physical evidence for a putative typology of factories through which the motivations, catalysts and development of Anglo-Indian trade might be better understood. In doing so the physical characteristics of the factories themselves are discussed and the significance of their architectural form and settings assessed. In Chapter 8 the third part of the thesis presents a discussion centred on the principal themes to emerge from this evidence. These include aspects of regional and intra-Asian trade, geography, indigenous society and polity, European mercantile and military rivalry, East India Company administration and proto-colonialism. Chapter 9 concludes the study by considering the veracity of the factory typology, reviewing the research aims, assessing the potential for archaeological fieldwork at the factory sites and identifying possibilities for further research in this field